Effectiveness of Vacuum Assisted Closure(VAC) Therapy for Infected Non Healing Wounds - Malik Zafar Iqbal, Naeem Ashraf, Ghulam Rasool, Muhammad Kamran Afzal, (Journal of Rawalpindi Medical College, 2013)
Background: To assess the effectiveness of vacuum assisted closure (VAC) therapy for healing of infected wounds. Methods: In this prospective case-control study, total of 25 patients with chronic non-healing wounds were recruited. Before the application of VAC, surgical debridement was performed to remove all the devitalized necrotic tissues as per requirement and the wound was packed with povodine/iodine. Wound dimensions were noted prior to and at the end of VAC, before the definitive treatment using skin graft or secondary closure was performed. Results: Diabetic Foot was the commonest cause (57%) followed by road traffic accident ( RTA) (43%). Wounds were present for about 4 weeks on average, 88% wounds were infected and 92% wounds needed prior surgical debridement under regional or general anaesthesia. VAC therapy was applied through continuous or intermittent suction on wounds. Dressing was changed every 2nd or 3rd day. It needed 4 dressings and 12 days on average for wounds to heal. All wounds showed improvement after application of VAC therapy, which were indicated by presence of healthy granulation tissue, absence of necrotic tissue and subsequent wound closure by partial thickness skin graft(PTSG) or secondary suturing or secondary healing. Conclusion: Vacuum aided wound closure has the advantage of rapid healing, easy application, safety and cost effectiveness. This method is recommended for chronic wound management.